ANALYSIS OF HISTORICAL GEOGRAPHICAL INFORMATION FOUND IN THE WORK OF "BOBURNOMA" - Orzubek O‘ralov (TADQIQOTLAR.UZ, 2024)
Annotation.  The  article  analyzes  the  geographical  location,  place-names, forests, rivers and other natural objects in "Boburnoma". Historical events and how they are covered by the author are also considered, as well as the importance of this information in the study of history and cultural heritage. Through the results of the research, it is aimed to create a broader idea about the historical-geographical aspects of the work and to create an opportunity to add it to modern scientific research.